Teachers challenges and experiences when planing and presenting agricultural sciences theory and practical lessons in Lebopo Circuit, Capricorn South District, Limpopo Province, South Africa - Shibambe, Left (My University, 2025)
Agricultural Sciences teachers should embrace theoretical and practical lessons during teaching and learning process to produce competent learners for the South African economy and agricultural industries. Agricultural Sciences teachers need to be well equipped with skills and knowledge of the subject to produce learners who will remain relevant in the South African economy and industries. The study has opted for qualitative research approach underpinned by interpretivism paradigm. The study was carried out in 5 secondary schools of Capricorn South. The purpose of this study was to explore teachers’ challenges and experiences when planning and presenting Agricultural Sciences theory and practical lessons in Lebopo Circuit, Capricorn South District, Limpopo Province, South Africa. It had been identified that Agricultural Sciences teachers are faced by numerous challenges when planning and teaching the subject. Purposive sampling was used in identifying five Agricultural Sciences teachers in Lebopo circuit who participated in the study. Data collection instruments employed in the study were document analysis, semi-structured interviews, field note and non-participating observation. Collected data were analysed through the use of interpretative analysis and document analysis for lesson plans. Clark and Peterson (1986) as well as Mitzel (1969) informed the conceptual framework that guided the study. The findings of the study revealed that most Agricultural Sciences teachers do not use lesson plans in teaching and learning. Furthermore, the study also established that some of teachers lack pedagogical strategies and assessment skills. The study also discovered that the lack of teaching and learning resources leads to poor practical lesson, failure to attain some of the lesson objectives and badly affect learners’ academic performance. The study has recommended that Agricultural Sciences teachers should attend content, policy and practical workshops to improve their skills in teaching and learning. Most important, teachers should undergo continuous profession development training on how to plan and teach theory and practical lessons. Furthermore, the study has also recommended that Agricultural Sciences should be introduced in primary and GET level in order to produce more and boost economy.
Thesis (M. (Science Education)) -- University of Limpopo, 2025
Keywords: Assessment; Practical skills and knowledge; Lesson planning; Presenting; Agriculture -- Study and teaching; Teachers -- South Africa -- Limpopo; Educational tests and measurements; Vocational education -- South Africa -- Limpopo